2005
DOI: 10.1175/jcli3338.1
|View full text |Cite
|
Sign up to set email alerts
|

Indian Ocean Sea Surface Temperature and El Niño–Southern Oscillation: A New Perspective

Abstract: Here we show that the [1976][1977]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
67
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 78 publications
10
67
0
Order By: Relevance
“…From positive correlation between the SAM and the SOI in the 1990s. Terray and Dominiak (2005) demonstrate a reduction in speed of the polar front jet in the South Pacific associated with the ENSO SST anomalies that also confirms the link between the ENSO and the SAM.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…From positive correlation between the SAM and the SOI in the 1990s. Terray and Dominiak (2005) demonstrate a reduction in speed of the polar front jet in the South Pacific associated with the ENSO SST anomalies that also confirms the link between the ENSO and the SAM.…”
Section: Discussionsupporting
confidence: 74%
“…12c) the southern branch of the horseshoe pattern is well marked. Terray and Dominiak (2005) relate this southern branch of the SST horseshoe pattern to the enhanced upper-level convergence brought about by the modulation of the regional meridional Hadley circulation. This upper-level convergence is associated with an upper-level low, which acts as a Rossby wave source region for the associated PSA pattern.…”
Section: Discussionmentioning
confidence: 95%
“…It is interesting to note that just before mid-1985 when the correlation sign changed, the Pacific climate underwent a climate shift (Graham 1994). The growth of ENSO was also different before and after the 1970s regime shift (Terray and Dominiak 2005).…”
Section: Resultsmentioning
confidence: 98%
“…Although the data length is quite short, it covers the period when the relationship between the UOHC and SST variability becomes more significant after the 1976/77 Pacific climate regime shift (Hasegawa and Hanawa 2003;Terray and Dominiak 2005).…”
Section: Datasetsmentioning
confidence: 99%
“…Webster et al 1998; showed that the interannual SSTA in the Indian and northwestern Pacific oceans are largely due to the remote ENSO forcing through the atmospheric bridge mechanism (Lau and Nath 1996), the presence of independent SSTA modes maintained by the local air-sea interactions has drawn great attentions recently (Saji et al 1999;Behera et al 2003;Terray and Dominiak 2005). For example, Tourre and White (1995) used limited subsurface data to show the presence of ENSO related eastward propagating SSTA and UOHCA patterns in the Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%